Auction design with endogenously correlated buyer types - Daniel Krähmer (Verein für Socialpolitik, 2010)
This paper studies optimal auction design when the seller can affect the buyers' valuations through an unobservable ex ante investment. The key insight is that the optimal mechanism may have the seller play a mixed investment strategy so as to create correlation between the otherwise (conditionally) independent valuations of buyers. The paper establishes conditions under which the seller can, in fact, extract the first best surplus almost fully.
Keywords: C72; D44; D82; 330; Auction; ex ante investment; full surplus extraction; correlation; mechanism design